Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.11646/zootaxa.4299.2.10
|View full text |Cite
|
Sign up to set email alerts
|

A new species of Olecryptotendipes Zorina from China (Diptera, Chironomidae)

Abstract: Olecryptotendipes arienus Yan & Wang sp. n. is described and illustrated as male imago from China. The generic diagnosis of Olecryptotendipes Zorina is amended. A key to the known adult males of the genus worldwide is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 1,171 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…These later identifications revealed that the species used for laboratory experiments in China was Chironomus sp. (according to Wang & Wang, 2011). Species used in Australian bioassays were Chironomus sp.…”
Section: Methodsmentioning
confidence: 99%
“…These later identifications revealed that the species used for laboratory experiments in China was Chironomus sp. (according to Wang & Wang, 2011). Species used in Australian bioassays were Chironomus sp.…”
Section: Methodsmentioning
confidence: 99%